A case of refractory ventricular fibrillation successfully treated with low-dose esmolol. Issue 3 (8th March 2019) - Hwang, Charles W; Gamble, Ginger; Marchick, Michael; Becker, Torben K
Abstract : Current advanced cardiac life support (ACLS) guidelines for the management of ventricular fibrillation (VF) and pulseless ventricular tachycardia is defibrillation. However, refractory VF, which is defined as VF that persists despite three defibrillation attempts, is challenging for all ACLS providers; the best resuscitation strategy for patients that persist in refractory VF remains unclear. We report on a 51-year-old man who presented to the emergency department with chest pain and subsequently went into witnessed VF cardiac arrest. Despite standard ACLS management consisting of high-quality cardiopulmonary resuscitation, serial epinephrine and serial defibrillation, the return of spontaneous circulation (ROSC) was unable to be achieved. Double sequential defibrillation (DSD) was attempted multiple times unsuccessfully. After administration of low-dose esmolol, he immediately achieved ROSC. DSD and β-blockade are increasingly recognised in the literature and practice for refractory VF. However, to the best of our knowledge, this is the first case of refractory VF that responded to low-dose esmolol β-blockade.